2022
DOI: 10.3389/fmed.2022.855869
|View full text |Cite|
|
Sign up to set email alerts
|

Relationship Between C-Reactive Protein/Serum Albumin Ratio, Neutrophil/Lymphocyte Ratio, and ANCA-Associated Vasculitis Activity: A Retrospective Single Center Cohort Study

Abstract: ObjectivesTo evaluate the role of C-reactive protein/albumin ratio (CAR), neutrophil/lymphocyte ratio (NLR), and mean platelet volume (MPV) in newly diagnosed AAV patients and examine their clinical significance.MethodsData from 79 untreated newly diagnosed AAV patients were collected and 76 health examination subjects were included in the healthy control group. All clinical characteristics of AAV patients were extracted from their medical records. The NLR, CAR, and MPV levels of AAV patients and the healthy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…It is because of this that many studies have been carried out for predicting visceral organ involvement, particularly in the GI and renal systems, using various indices and laboratory parameters. However, as far as we know, in recent studies, no assessment has been made regarding the place of SII and CAR in determining prognosis in illnesses such as cancer, MI, Behcet's Disease, and ANCA-associated vasculitis (15,19,20,(27)(28)(29). We found in our study that CAR was not significantly effective in determining prognosis for visceral involvement in patients with IgAV, but SII was a significant predictor of visceral involvement.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…It is because of this that many studies have been carried out for predicting visceral organ involvement, particularly in the GI and renal systems, using various indices and laboratory parameters. However, as far as we know, in recent studies, no assessment has been made regarding the place of SII and CAR in determining prognosis in illnesses such as cancer, MI, Behcet's Disease, and ANCA-associated vasculitis (15,19,20,(27)(28)(29). We found in our study that CAR was not significantly effective in determining prognosis for visceral involvement in patients with IgAV, but SII was a significant predictor of visceral involvement.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies have shown that the NLR value is higher in patients with renal and systemic involvement in IgAV than in patients without renal and systemic involvement (3,22,44,46). In recent years, SII, which uses neutrophils, platelets, and lymphocytes together, and the CAR index, which evaluates CRP and albumin together, have attracted the attention of researchers and been used to evaluate disease pathogenesis and severity of inflammation in many diseases (15,19,21,(27)(28)(29)(47)(48)(49)(50). Since CAR provides the opportunity to evaluate increased CRP and decreased serum albumin together in chronic inflammation, it has provided researchers with a twoway perspective.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is part of the innate immunity involved in nonspecific opsonization and neutralization of antigens, in contrast to the antigen-specific adaptive/acquired immunity maintained by antibodies [ 25 ]. While elevated baseline CRP at disease onset of AAV has already been described as a determinant of poor long-term outcomes, its clinical implications at disease onset of AAV with respect to vasculitis manifestations and complement system activation remain elusive [ 21 , 22 , 23 , 24 ]. Therefore, in this study, we aimed to systematically describe clinicopathological findings in association with baseline CRP levels at disease onset of AAV in kidney-biopsy-confirmed severe ANCA-associated renal vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…CRP primarily binds to phosphocholine-containing molecules, and CRP–phosphocholine complexes activate the classical pathway of the complement system [ 15 , 16 , 17 , 18 , 19 , 20 ]. Elevated baseline CRP at disease onset of AAV has already been described as a determinant of poor long-term outcomes [ 21 , 22 , 23 , 24 ]. However, its clinical implications at disease onset of AAV, with respect to vasculitis manifestations and complement system activation that might also affect long-term outcomes, remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Salman et al evaluated 338 adult COVID‐19 patients and showed that the patients with high CRP and hypoalbuminemia had severe progression of the disease and high rates of admission to the intensive care unit, intubation, and mortality 34 . While some previous studies have shown that the CAR index predicts prognosis in inflammatory diseases, studies on this subject in MIS‐C patients are limited 17,18 . The rapid course and intense inflammatory process in the first few days of the disease suggest that the CAR index may be a useful marker.…”
Section: Discussionmentioning
confidence: 99%